Razvoj zdravstvene nege na Očesni kliniki v Ljubljani - Nendl, Tatjana (Obzornik zdravstvene nege, 2002)
The article describes historical development of the Ophtalmological Hospital in Ljubljana, and development of nursing care which was parallel to it. The purpose of the article is to highlight some developments in the field of nursing care in the past and nowadays. In conclusion, the article stresses theimportance of familiarity with the past, of education, knowledge and research for the development of nursing care.
Keywords: Bolniški oddelki; Eye Diseases; History; Hospital Departments; Hospitalizacija; Hospitalization; Nursing; Očesna klinika (Ljubljana); Očesne bolezni; razvoj; Trends; zdravstvena nega; zgodovinski pregledi